Increased incidence of weight-loss-associated humane endpoints in rats administered buprenorphine slow-release LAB formulation following traumatic brain injury: a retrospective study - Lilova, Radina L.; Hernandez, Martina; Kelliher, Corrina; Lafrenaye, Audrey (Frontiers in Neurology, 2024)
Traumatic brain injury (TBI) remains a significant global public health epidemic with adverse health and cost implications. Due to its complex, heterogeneous nature and wide-ranging impacts, definitive TBI treatments remain elusive. As such, continued laboratory research using animal models is warranted. In accordance with guidelines set forth for the humane treatment of research animals, TBI animal models are often administered analgesics for pain management. The choice of drug, timing, dose, and formulation of analgesic can vary depending on the study’s unique needs and can potentially and unintentionally influence experimental results. In TBI studies utilizing rats as animal models, buprenorphine is a common analgesic administered. In addition to pain management in such studies, investigators must also monitor the research animals post-operatively and make the decision for humane euthanasia before intended experimental survival timepoint if the animals are assessed to be excessively suffering. This study investigated the differences in adult, male Sprague Dawley rats used for various TBI studies that reached weight-loss-induced humane endpoints following a single administration of buprenorphine slow-release LAB (bup-SR-LAB) or buprenorphine slow-release HCl (bup-SR-HCl). Our findings indicate that TBI-induced rats receiving bup-SR-LAB in conjunction with a secondary surgical insult such as artificial intracranial pressure elevation and/or osmotic pump implantation reach a weight-loss-induced humane euthanasia endpoint more often compared to sham-injured rats. When stratifying into the same groups, we did not find this pattern to hold true for rats administered bup-SR-HCl. Overall, this study contributes to the limited body of literature addressing different analgesic formulations’ effects on laboratory animals.